Girls Entrepreneurship Education Concept At Rumah Singgah Anak Perempuan Garuda - Rr. Vemmi Kesuma Dewi; Endang Sondari (Kontigensi : Jurnal Ilmiah Manajemen, 2021)
The impact of the 4.0 industrial revolution era is enormous on the behavior of the people, including children, who massively switch to technology; this is a product of change driven by developed countries as holders of the world constellation in the fields of science and technology and the economy. The success of developed countries cannot be separated from the role of educational institutions. The era of globalization is currently being experienced by all people in the world, including in Indonesia. Global challenges with advances in science and technology. The concept of entrepreneurial education for girls in open houses causes competition and faster and more competitive movements, which directly impact the world of education. Entrepreneurship is not only a world of adults, but it can also be a part of the world of children. The difference is, entrepreneurship in children cannot be carried out alone. However, it requires guidance and support from adults, parents, and teachers. Children who know the world of entrepreneurship from an early age will find it useful for future provisions. Education is an integral part of the life of society, nation, and state. One of the factors taken to improve the quality of life of the Indonesian nation is to increase the attitude of independence in the future.